Characterisation of dust aerosols in the infrared from IASI and comparison with PARASOL, MODIS, MISR, CALIOP, and AERONET observations - Peyridieu, S.; Chédin, A.; Capelle, V.; Tsamalis, C.; Pierangelo, C.; Armante, Raymond; Crevoisier, C.; Crépeau, L.; Siméon, M.; Ducos, F.; Scott, N.A. (Atmospheric Chemistry and Physics, 2013)
International audience Infrared Atmospheric Sounder Interferometer (IASI) observations covering the period from July 2007 to December 2011 are interpreted in terms of monthly mean, 1°×1°, 10 µm dust Aerosol Optical Depth (AOD), mean altitude and coarse mode effective radius. The geographical study area includes the northern tropical Atlantic and the northwest Arabian Sea, both characterised by strong, regular dust events. The method developed relies on the construction of Look-Up-Tables computed for a large selection of atmospheric situations and observing conditions. At a regional scale, a good agreement is found between IASI-retrieved 10 µm AOD and total visible optical depth at 550 nm from either the Moderate resolution Imaging Spectroradiometer (MODIS/Aqua or Terra), or the Multi-angle Imaging SpectroRadiometer (MISR), or the Polarization and Anisotropy of Reflectances for Atmospheric Science coupled with Observations from a Lidar (PARASOL). Taking into account the ratio existing between infrared and visible AODs, the diversity between the different 550 nm AODs is similar to the difference between these and the IASI AODs. The infrared AOD to visible AOD ratio, partly reflecting the varying distribution of the dust layer between the dust coarse mode particles seen by IASI, and the fine mode seen by the other instruments, is found to vary with the region observed with values close to already published values. Comparisons between the climatologies of the 10 µm IASI AOD and of the PARASOL non-spherical coarse mode AOD at 865 nm, both expected to be representative of the dust coarse mode, lead to conclusions differing according to the region considered. These differences are discussed in the light of the MODIS Angström exponent (865-550 nm). At local scale, around six Aerosol Robotic Network (AERONET) sites, close or far from the dust sources, a similar satisfactory agreement is found between IASI and the visible AODs and the differences between these products are shown and analysed. IASI-retrieved dust layer ...